“Bie zai tiqi” and You Mean the World to Me: Two Subversive Sinophone Malaysian Metatexts - Paoliello Antonio (Open Cultural Studies, 2020)
This article aims at exploring the subversive nature of two Sinophone Malaysian cultural products, namely “Bie zai tiqi” (2002) a short story by Ho Sok Fong and You Mean the World to Me (2017), a full-length feature film by director Saw Teong Hin. I argue that, despite their differences, both fictional products use powerful metafictional and metanarrative devices to challenge factuality. In doing so, they not only blur the fine line between fiction and reality, but they also question cultural power dynamics and ethnic politics in Malaysia. Moreover, they defy the truthfulness of Mandarin as the preferred Sinitic cultural language as well as the idea that, in Malaysia, literature and film can be considered Malaysian only if produced in Malay, the official language of the country. By performing an analysis of the linguistic choices made by Ho Sok Fong and Saw Teong Hin, I will suggest that both the short story and the feature film analysed in this article use metafiction and metanarration to subvert widely-accepted, yet problematic, notions of national culture and common ethnic language.